Zoneamento ambiental do Município de Aquiraz - Ceará - Lopes, José Lidemberg de Sousa (2006)
The Metropolitan Region of Fortaleza (RMF) is composed by thirteen cities, where is call the attention of Aquiraz. The city has a excellent resort area and a big importance in socioculture and historics aspects. It was one of the first village of Ceará, and it was founded in 1699, with was also the capital of the state until 1726. The urban local development has been disorganized in the last decades, the fact is, insert of turismon in its coast, and it is unable with alow capacity of the natural suppots, configuring unsustainable and et environment ambience. Considering as a turistic region, it is preoccupy, been necessart to create a better control of the nature of the region by the users. The environmental zoning in this work it is to plan of adequate form the use of the ground based in the management of the interests and the social and economic necessities in accord with the preservation of the environment and the natural characteristics of the city. The same is one great instrument planning where use to be analized in differents ways: social, ambiental, economical and institucional, and promove alternatives of use and occupation of the land to recreate the city. The methodo used to get the real objective, englobed zonal maps in ambiental unities and others themes (geologic/geomorphologic) since than the images from satelities LANDSAT and SPOT and fotografies under position of maps, secundaries listes gets in publics department, bibliographie, informations by the local populations. This prociduries mede easy to create maps, geologic/geomorphologic, of use and occupation the earth and the environmental zoning to analize the dynamic and the working of each ambiental unity of the city Aquiraz wich is located by map of this job. As a result of this job was confectionated the environmental zoning map of Aquiraz wich was divided in five ambiental unities and restrictions areas of occupation: unit I Littoral Plain (zoning with serious restrictions to the occupation); unit II Sub-Littoral Plain (improper zoning to the occupation); unit III between tray zoning Pré-Littoral and Peripheral Depression (improper zoning to the occupation); unit IV Strativism reserve of the plug (zoning used more under control in its occupation) and unit V Fluvial Plain Localities of the Indians Jenipapo-Kaninde/ locality Quilombolas (zoning used more without official regulation). With proposal in the ambient units above one expects that it has a reduction of the ambient degradation and protection of the local biodiversity of the city of Aquiraz in the State of the Ceará